Growth of oyster (Crassostrea sp.) with different stocking density in Alue Naga waters, Banda Aceh Indonesia. Issue 1 (February 2021) - Rusydi, I; Dewiyanti, I; Maisuri, M; Putra, D F; Octavina, C; Nurfadillah, N; Wulandari, W
Abstract: Oyster ( Crassostrea sp.) is one of the potential bivalves that have big potency to increase Indonesian economic income. This study aimed to investigate the growth of oysters ( Crassostrea sp.) with different densities, and to determine the effect of different stocking densities on growth and survival in the submerged raft method in oyster aquaculture in Alue Naga district, Indonesia. A completely randomized design model (CRD) was used with three treatments and triplications. There were three different stocking densities namely 25, 30, and 35 ind/1500 cm2. The results showed that the absolute length and weight of oysters with a density of 25, 30 and 35ind/1500 cm 2 were ranged from9.49 mm and 10.60 grams, 4.83 mm and 9.13 grams and 4.62 mm and 5.76 grams respectively. It is concluded that the best growth oyster in this study was at 25 ind / 1500 cm 2 stocking densities.